Working in Public Administration During Nonwork Time During the COVID-19 Pandemic - Špela Mar; Jernej Buzeti (Central European Public Administration Review)
With the outbreak of Covid-19, a pandemic was declared in March 2020 and countries introduced various measures to overcome it. As a result, employees worked more intensively from home with the use of information and communication technologies (ICT), which significantly affected the way of work, the length of the working day, and the time reserved for rest. The purpose of this article is to examine whether, during the pandemic, public employees in the Slovenian public administration worked during nonwork time. This is the first research of this kind in the Slovenian public administration. The research applied the quantitative method and an online questionnaire conducted in February 2021, whereby data from 1676 public administration employees were obtained. The results of the research show that at the time of the Covid-19 pandemic, 80% of the respondents performed work during nonwork time. In fact, public employees quite often worked late in the afternoon after working hours and on weekends. Interestingly, about 10% of public employees even worked during annual leave and sick leave. The results of the research contribute to theoretical and practical knowledge about work related activities during nonwork time.